Observation of the geometric phase effect in the H+HD→H2+D reaction below the conical intersection - Daofu Yuan; Yin Huang; Wentao Chen; Hailin Zhao; Shengrui Yu; Chang Luo; Yuxin Tan; Siwen Wang; Xingan Wang; Zhigang Sun; Xueming Yang (Nature Communications, 2020)
The geometric phase effect associated with a conical intersection between the ground and first excited electronic state has been predicted in the H3 system below the conical intersection energy. The authors, by a crossed molecular beam technique and quantum dynamic calculations, provide experimental evidence and insight into its origin.